Accuracy of Genomic Evaluations of Juvenile Growth Rate in Common Carp (Cyprinus carpio) Using Genotyping by Sequencing - Palaiokostas, Christos; Kocour, Martin; Prchal, Martin; Houston, Ross D. (Frontiers in Genetics, 2018)
Cyprinids are the most important farmed fish globally in terms of production volume, with common carp (Cyprinus carpio) being one of the most valuable species of the group. The use of modern selective breeding methods in carp is at a formative stage, implying a large scope for genetic improvement of key production traits. In the current study, a population of 1,425 carp juveniles, originating from a partial factorial cross between 40 sires and 20 dams, was used for investigating the potential of genomic selection for juvenile growth, an example complex production trait. RAD sequencing was used to identify and genotype SNP markers for performing parentage assignment, construction of a medium density genetic map (12,311 SNPs), genome wide association (GWAS) and genomic selection (GS). A moderate heritability was estimated for body length of carp at 120 days (as a proxy of juvenile growth) of 0.33 (s.e. 0.05). No genome-wide significant QTL were identified using a single marker GWAS approach. Genomic prediction of breeding values outperformed pedigree based prediction, resulting in 25% improvement in prediction accuracy. A reduction in SNP density lowered genomic prediction accuracy, although it still outperformed pedigree-based prediction. These results point to the potential for GS to improve economically-important traits in common carp breeding programs.